Investigation of Epoxidized Palm Oils as Green Processing Aids and Activators in Rubber Composites - DongJu Lee; Sung Ho Song (International Journal of Polymer Science)
Epoxidized palm oil (EPO) is environmentally friendly, biodegradable, and a relatively less costly processing aid. In this study, we investigated the suitability of EPO in place of aromatic processing oils in styrene butadiene rubber. The curing properties, mechanical properties, abrasion resistance, and heat buildup properties of rubber composites with EPO were compared with those of the standard with aromatic oils. The rubber composites with EPO showed enhanced mechanical properties including modulus, tensile strength, and elongation at break. This is ascribed to the improved dispersion of fillers in the rubber matrix and interaction between the filler and the polymer. Furthermore, EPO in the rubber matrix showed remarkable abrasion resistance, rebound resilience, and heat buildup at low loadings. EPO in a rubber composite presents feasibility as a renewable raw material that can serve as an alternative to petrochemical oils in various applications.